Mensuração de eficiência : um novo exame aplicado aos portos públicos brasileiros - Rios , Cláudio Oliveira (2015)
This paper deals with an investigation of the inefficiency of Brazilian public ports, given the recurring and growing questioning this sector has suffered in recent years. So there was a bibliographical reference on the routines and peculiarities of Brazil’s port system, considering its History and the current context. Variables were enrolled according to their market relevance, then it was proposed the inclusion of unpublished variables in literature and it turned out to be extremely significant to measure the efficiency of national public ports. It was applied, as analysis methodologies, Data envelopment analysis (DEA) and the Stochastic Frontier Analysis (SFA), and in each one it was demonstrated its features and results. Thus, it was formulated six models, and in each one was possible to see which public ports in the sample are the most efficient or inefficient and which variables are significant for their performance. This way, it could be concluded that all proposed formulations suggested a high level of inefficiency of national public ports in this period.